TOTAL PRODUCTIVE MAINTENANCE (TPM) TO EVALUATE INCREASED PRODUCTION EFFICIENCY IN CAPSULE MACHINES FILLING PT ALB - Jeni Rosadi, Tiara
Total Productive Maintenance (TPM) is an innovative approach to maintenance techniques that optimizes equipment effectiveness through continuous improvement involving product and service processes. TPM includes Autonomous Maintenance (AM) carried out by machine operators as well as Planned Maintenance (PM) to reduce unplanned downtime. The purpose of TPM using AM and PM is to find out the six big losses found in production machines. The method used is carrying out AM and PM to increase the Overall equipment effectiveness (OEE) value which is used as a measuring tool in implementing total productive maintenance (TPM) at PT ALB. Evaluation of this capsule filling machine is measured through availability, performance rate and rate of product quality as well as determining the components of the six big losses. The results before TPM were carried out showed an OEE value of 53.16% in November and December 2021. Evaluation data used capsule filling machine production data, maintenance data, and direct interviews with operators and related officials. The research results show that there is a level of non-production time that must be improved. Factors that influence the effectiveness of capsule filling machines include breakdown (equipment damage) and setup (equipment adjustment), resulting in decreased machine performance, high machine idle levels and low productivity. However, after intervening on the machine for 8 months, namely January to September 2022, there was an increase in OEE of more than 75%, as well as a decrease in the percentage of six big losses in downtime losses and speed losses. So the average OEE value during October 2022 – March 2023 is more than 85%. The high OEE value is a contribution from the average Performance Rate and Availability values during October 2022 – March 2023 of 91.51% and 92.34%. With the intervention of the TPM approach, especially by carrying out AM and PM, it can increase OEE from 68,01% to 86.23% exceeding the standard value